Overview of Cadmium Levels in the Blood of Smoking Gas Station Workers in Comal District, Pemalang Regency - Khotimah, Khusnul; Kumala, Izza Ratna (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & objectives: Cigarettes are addictive substances that contain harmful chemicals, such as nicotine, tar, carbon monoxide, acetone, benzene, lead, and cadmium. Cadmium is a heavy metal contained in cigarettes that has a fairly high toxicity. Cadmium that enters the body will accumulate for a long time in the liver and kidneys. In the body, cadmium is absorbed into the bloodstream and then distributed to tissues, where it can bind to various types of molecules, such as proteins, phospholipids, purines, enzymes, and porphyrins. Gas station workers are frequently exposed to vehicle exhaust, which also contains cadmium, originating from vehicle activities such as fuel combustion and the erosion of vehicle components. This study aims to determine the cadmium levels in the blood of respondents who are smokers and work at gas stations in Comal District, Pemalang Regency. Methods: This study is a descriptive study. Samples were taken using purposive sampling from a population of 17 people, with 9 respondents meeting the inclusion and exclusion criteria. Results: Blood sample testing using an Atomic Absorption Spectrophotometer (AAS) showed that two respondents had cadmium levels of 0.2 µg/dL or below the normal value according to the CDC (Centers for Disease Control and Prevention), while the other seven respondents had cadmium levels below the LOD (Limit of Detection) on the AAS device. Conclusion: The cadmium levels were 100% within the normal range. The highest cadmium levels were found in samples S6 and S8, at 0.2 µg/dL.